HAPTIC FEEDBACK AND PRESENCE IN VIRTUAL REALITY: AN EXPERIMENTAL STUDY ON THE IMPACT OF TACTILE SENSATIONS ON USER IMMERSION - Ethan Tan; Riko Kobayashi; Lena Hoffmann (Yayasan Adra Karima Hubbi, 2025)
The integration of haptic feedback into Virtual Reality (VR) systems has gained significant attention as a means to enhance user immersion and presence. While visual and auditory feedback have been extensively studied, the impact of tactile sensations on users' experience of immersion in VR environments remains underexplored. This study investigates the effects of different types of haptic feedback on user presence and immersion in VR. The research aims to determine how tactile sensations, such as vibration and force feedback, influence users' engagement and emotional involvement in virtual environments. A mixed-methods approach was used, involving 90 participants who were exposed to three conditions: no haptic feedback, basic haptic feedback (vibration), and advanced haptic feedback (force and texture simulation). Quantitative data were collected through immersion and presence questionnaires, while qualitative data were gathered through post-experiment interviews. The results show that advanced haptic feedback significantly improves both user presence and immersion compared to the other two conditions. Participants in the advanced feedback group reported higher emotional engagement, greater realism, and improved cognitive involvement. These findings suggest that haptic feedback plays a critical role in enhancing VR experiences by fostering a stronger sense of being